ZnO-based chemi-resistive sensors for CO2 detection: a review. Issue 6 (11th October 2022) - Stramarkou, Marina; Bardakas, Achilleas; Krokida, Magdalini; Tsamis, Christos
Abstract : Purpose: Carbon dioxide (CO2 ) has attracted special scientific interest over the last years mainly because of its relation to climate change and indoor air quality. Except for this, CO2 can be used as an indicator of food freshness, patients' clinical state and fire detection. Therefore, the accurate monitoring and controlling of CO2 levels are imperative. The development of highly sensitive, selective and reliable sensors that can efficiently distinguish CO2 in various conditions of temperature, humidity and other gases' interference is the subject of intensive research with chemi-resistive zinc oxide (ZnO)-based sensors holding a privileged position. Several ZnO nanostructures have been used in sensing applications because of their versatile features. However, the deficient selectivity and long-term stability remain major concerns, especially when operating at room temperature. This study aims to encompass an extensive study of CO2 chemi-resistive sensors based on ZnO, introducing the most significant advances of recent years and the best strategies for enhancing ZnO sensing properties. Design/methodology/approach: An overview of the different ZnO nanostructures used for CO2 sensing and their synthesis methods is presented, focusing on the parameters that highly affect the sensing mechanism and, thus, the performance of CO2 sensors. Findings: The selectivity and sensitivity of ZnO sensors can be enhanced by adjusting various parameters during their synthesis and by doping or treating ZnO with suitable materials. Originality/value: This paper summarises the advances in the rapidly evolving field of CO2 sensing by ZnO sensors and provides research directions for optimised sensors in the future.